The Post-Pandemic Changes of Dark Tourism Industry - Radzevičius, Martynas (Vilnius University Open Series, 2022)
Dark tourism is a segment of tourism that has been growing in recent decades and is strongly associated with tragedy and mystery. As a result, 2020 was strongly marked by the pandemic of the new coronavirus (COVID-19). This paper presents a reflection on the role of dark tourism in the pandemic and post-pandemic period and analyses impact of the COVID-19 pandemic on tourism industry. The paper discusses the global context of the pandemic situation that has an important impact on re-directing and tracing eventually new tourism trajectories of the (post)pandemic time. The shift that occurred in pandemic time are like catalysts for re-enforcement and raised interest into slow movements and ‘new normal’ tourism. Instead of seeking to ‘go back to business as usual’, the author argues to reconsider the trajectories that emerged during the time of the pandemic and to envisage other approaches towards more sustainable tourism.
Keywords: Post-pandemic tourism; ‘New Normal’; Dark Tourism; Tourism Management; Sustainable development